The time-varying degree of inflation expectation anchoring in Bolivia - Mauricio Mora Barrenechea; Juan Carlos Heredia Gómez; David Zeballos Coria (Inter-American Development Bank (IDB), 2018)
This paper analyzes the time-varying degree of inflation expectations anchoring in Bolivia and, more precisely, whether inflation expectations have been in line with the inflation objectives announced by the Central Bank of Bolivia (BCB, for its acronym in Spanish) and if they have become better anchored over time. Two considerations are particularly relevant in this regard. First, the main sources of information are the BCB survey and Focus Economics survey, which only have data for short and medium-term inflation expectations. Second, monetary policy in Bolivia is under a monetary-targeting regime, so BCB projections represent the main references. The anchoring degree analysis of short-term inflation expectations was performed considering BCB projections, while the medium-term analysis used an implicit inflation target. In both cases, the results indicate there is a high degree of anchoring of inflation expectations in Bolivia, especially during the last four years. This study considers information from July 2005 to June 2017, with monthly frequency.
Keywords: E31; E52; E58; C32; 330; Inflation expectations; Anchoring degree; BCB projections; Timevarying parameters model